L04 Shaping The Huntington's Disease Journey: A Managed Care Pathway For Scotland. (17th September 2014) - Rae, D; Eden, J; Miedzybrodzka, Z
Abstract : Background: Across Europe management of long-term conditions and complex rare diseases has become a major focus of policy development. Such policies promote person–centred, co-ordinated multi-disciplinary care delivered through partnership working within managed care networks to ensure independent living and better quality of life. The Scottish Huntington's Association has partnered with government agencies to develop a model care pathway for Huntington's disease integrating health and social care services that has been successfully implemented across Scotland. Aims: The aim of this pathway is allow those living with HD to maximise quality of life and to receive safe, effective and person centred care utilising available resources. Methods: A draft pathway was developed during a one day stakeholders' meeting to identify the approaches, resources and challenges that may arise for people living with HD. The pathway was widely consulted prior to implementation. Results: An outline of the managed care pathway is presented here. Conclusions: Adoption of this managed care pathway will streamline service provision and provide high quality and cost effective healthcare that is of high quality and cost effective within the constraints of locally available resources. It suggests a model of effective support service delivery throughout the trajectory of the disease that could be implemented in other European settings.